Actual situation and reason of shortage of water in Red River delta region - Lan, Vu Thi Thu; Son, Hoang Thanh; Tuan, Bui Anh (Vietnam Journal of Earth Sciences, 2014)
Red River delta is the region with developed wet rice civilization for a long time and is one of two major rice bowl of the country due to plentiful resources of land and water. However, in recent years, drought, water shortage occurs continuously across the board, especially in the first decade of the 21st century has severely affected economic - socialdevelopment. Drought, lack of water in the Red River delta appears constantly do not follow the general rule and our assessment shows that drought, lack of water is directly related to the lowering of water levels in the Red River downstream in the years from 2004 to 2010. The statistical characterization of minimum water level in the calculated periods showed the strong downward trend of minimum water level during this period when there are many upstream reservoirs participate flow regulation compared with other periods.